Patient-Derived Organoid Models of Human Neuroendocrine Carcinoma - Dijkstra, Krijn K.; van den Berg, José G.; Weeber, Fleur; van de Haar, Joris; Velds, Arno; Kaing, Sovann; Peters, Dennis D. G. C.; Eskens, Ferry A. L. M.; de Groot, Derk-Jan A.; Tesselaar, Margot E. T.; Voest, Emile E. (Frontiers in Endocrinology, 2021)
Gastroenteropancreatic neuroendocrine carcinoma (GEP-NEC) is a poorly understood disease with limited treatment options. A better understanding of this disease would greatly benefit from the availability of representative preclinical models. Here, we present the potential of tumor organoids, three-dimensional cultures of tumor cells, to model GEP-NEC. We established three GEP-NEC organoid lines, originating from the stomach and colon, and characterized them using DNA sequencing and immunohistochemistry. Organoids largely resembled the original tumor in expression of synaptophysin, chromogranin and Ki-67. Models derived from tumors containing both neuroendocrine and non-neuroendocrine components were at risk of overgrowth by non-neuroendocrine tumor cells. Organoids were derived from patients treated with cisplatin and everolimus and for the three patients studied, organoid chemosensitivity paralleled clinical response. We demonstrate the feasibility of establishing NEC organoid lines and their potential applications. Organoid culture has the potential to greatly extend the repertoire of preclinical models for GEP-NEC, supporting drug development for this difficult-to-treat tumor type.